SINGULARITY CONFIGURATION AND MECHANICS UNLOADING ANALYSIS FOR 3-SPS/S SPHERICAL PARALLEL MECHANISM OF HIP JOINT - HOU YuLei; LI ZhiSen; WEI XiaoChen; ZHOU ZhiYu; ZHAO LiuJian; ZENG DaXing (Jixie qiangdu)
Combined with the actual structure and function characteristics of the human hip joint,3-SPS/S（ S for spherical pair,P for prismatic pair） spherical parallel mechanism is chosen as the prototype for the hip joint. After the inverse kinetic solution was solved,the singularity trajectory equations were established and the singular tracks were plotted. The static equilibrium equations of each component of the mechanism were established using the vector method. The curves of the exerted force on branches with the variety of poses were plotted by numerical examples,and then the mechanics unloading effect of the middle limb was analyzed. Through simulation analysis of the mechanism with ADAMS software,the force-time curves of the hinges fixed to the mechanism ’s branches corresponding to prescribed trajectory were obtained,which verified mechanics unloading function of mechanism. The research contents should possess certain theoretical guiding significance for the development and control of the hip joint of the humanoid robot.